2018
DOI: 10.1177/2516865718811117
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Chromatin: Role(s) of Methyl-CpG-Binding Protein ZBTB38

Abstract: DNA methylation plays an essential role in the control of gene expression during early stages of development as well as in disease. Although many transcription factors are sensitive to this modification of the DNA, we still do not clearly understand how it contributes to the establishment of proper gene expression patterns. We discuss here the recent findings regarding the biological and molecular function(s) of the transcription factor ZBTB38 that binds methylated DNA sequences in vitro and in cells. We specu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…We did not observe particular enrichment in GO pathways for APH UP genes (FDR > 0.01). Nevertheless, we noticed an up-regulation of the transcription factor gene ZBTB38 which is a biomarker for prostate cancer (59) and that plays an important role in the regulation of DNA replication, cell cycle and cell fate (60,61). Importantly, the expression of genes that fell inside aRTIL was not affected by low replication stress (Figure 4b).…”
Section: Low Replication Stress Impacts the Regulation Of Genes Involmentioning
confidence: 94%
“…We did not observe particular enrichment in GO pathways for APH UP genes (FDR > 0.01). Nevertheless, we noticed an up-regulation of the transcription factor gene ZBTB38 which is a biomarker for prostate cancer (59) and that plays an important role in the regulation of DNA replication, cell cycle and cell fate (60,61). Importantly, the expression of genes that fell inside aRTIL was not affected by low replication stress (Figure 4b).…”
Section: Low Replication Stress Impacts the Regulation Of Genes Involmentioning
confidence: 94%
“…It suggests that monitoring ZBTB38 SNP and mRNA status might improve the diagnosis and care of prostate cancer patients. The development of immunochemistry assays to monitor ZBTB38 protein levels in prostate specimens might also be valuable, as the protein is tightly regulated by ubiquitination [31,32,40], and its cellular abundance may differ from its mRNA expression.…”
Section: Zbtb38 and Its Paralogs Zbtb4 And Kaiso/zbtb33 Are Involved In Prostate Cancermentioning
confidence: 99%
“…In bladder cancer cells, ZBTB38 promotes cell migration and invasion, in part, by regulating Wnt/β-catenin signalling [38]. It was also showed that down-regulation of ZBTB38 potentiates the efficacy of anti-cancer DNA demethylating agent 5-azacytidine while causing heightened levels of reactive oxygen species (ROS) [32,33,40]. Interestingly, association between prostate cancer risk and ROS levels has been observed and it is thought that ROS contribute to the development and progression of the disease [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…ZBTB38, also known as CIBZ (CtBP-interacting BTB zinc finger protein), is another member of the BTB-ZF family and can function either as a transcriptional repressor or activator [ 14 ]. In contrast to other BTB-ZF factors that bind to similar DNA sequences, ZBTB38-mediated transcriptional regulation occurs by binding primarily to specific methylated CpG sequences and recruiting repressors or activators [ 15 19 ]. The uniqueness of ZBTB38 binding sites relative to other BTB-POZ factors led us to speculate that this factor would have a functionally important and non-redundant role in B cell responses.…”
Section: Introductionmentioning
confidence: 99%